The Cambrian brachiopod fauna from the first-trilobite age Shuijingtuo Formation in the Three Gorges area of China - Zhang, Zhi-Fei; Zhang, Zhi-Liang; Li, Guo-Xiang (李国祥); Holmer, Lars E. (Palaeoworld, 2016)
The Yangtze platform of South China offers evidence within its Ediacaran-Cambrian geological record of the Cambrian explosion and diversification events in metazoan history. To understand the explosive radiation of animals and the environments in which it took place, the basal Cambrian fauna succession of the Aijiahe section in the Three Gorges area, western Hubei Province, has been studied, revealing the earliest brachiopod fauna (Tsunyidiscus trilobite Zone) in this region, which was dominated numerically by acrotretoids. This is accompanied by abundant skeletal fossils including minute well-preserved phosphatized archaeocyath cups and an assortment of abundant sponge spicules, chancelloriids, mollusks, hyoliths, and bradoriids, retrieved by acid-etching limestone interbeds in the black shale-dominated Shuijingtuo Formation (Series 2). The brachiopods comprise two species of acrotretoids, two types of botsfordiids (Botsfordiidae gen. et sp. indet. A and B), and four species of linguloids. Of the latter, Spinobolus popovin. gen. n. sp. is strikingly distinctive and typified by spine-like ornamentation seen for the first time in the lower Cambrian; the remaining three linguloid genera, Palaeobolus, Eoobolus, and Lingulellotreta, have a trans-paleocontinental distribution. The Three Gorges Shuijingtuo brachiopod assemblage differs from that of the upper Atdabanian Stage (Cambrian Stage 3) in Siberia and South China, but shows great similarities with those discovered in the Tsanglangpuan (equivalent to Botoman or Stage 4) Stage of eastern Yunnan Province, Siberia, and South Australia, suggesting a much more prolonged sedimentary hiatus in basalmost Shuijingtuo Formation of the Three Gorges area than previously expected. The presence of such unconformities provides a caveat to stable isotope-based correlations that involve a number of discussions of global ocean geochemical changes across the time interval that witnessed Cambrian explosion of metazoans. (C) 2015 Elsevier B.V. and Nanjing Institute of Geology and ...